The Effect of Learning Independence and Academic Ability on Students' Critical Thinking Ability and Self-Efficacy as Intervening Variables - Santika, Fiska; Gusnardi; Makhdalena (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to determine the effect of learning independence and academic ability on students' critical thinking skills and self-efficacy as variables at SMP Muhammadiyah 1 Teluk Kuantan Kuantan Singingi Regency. The population in this study were 349 students of SMP Muhammadiyah 1 Teluk Kuantan, Kuantan Singingi Regency, Riau Indonesia. The sampling technique used was proportional random sampling of 186 students. Data measurement using questionnaires, interviews and documentation. Data analysis used with path analysis. The results of research based on path analysis show that learning independence and academic ability affect students' critical thinking skills mediated by self-efficacy.